Public-Private Partnership Units : Lessons for their Design and Use in Infrastructure - World Bank and PPIAF (World Bank, Washington, DC, 2021)
This report originated as part of a joint initiative between the Public Private Infrastructure Advisory Facility (PPIAF) and the East Asia and Pacific Sustainable Development Department of the World Bank. This paper defines a public-private partnership (PPP) as an agreement between a government and a private firm under which the private firm delivers an asset, a service, or both, in return for payments contingent to some extent on the long-term quality or other characteristics of outputs delivered. It uses a broad definition of PPP because of the different goals of each country's PPP strategy. This paper seeks to answer the question of whether specialist public-private partnership (PPP) units have contributed to successful PPPs.